Thermal storage unit with NEPCM involving numerical unsteady simulation - Mahmoud M. Selim; Ali Basem; Wissam H. Alawee; Awad Mousa; Abed Saif Alghawli (Case Studies in Thermal Engineering, 2022)
In current study, the channel for purpose of air ventilating has been suggested with considering containers of paraffin. To attain faster process, nanoparticles (TiO2) were mixed with RT25 and single phase formulations were utilized which means that uniform concentration of NEPCM exist in all over the zones of paraffin. There exist 2 variable factors: 1) vertical distance of containers (b); 2) fraction of powders with nano-sized (φ). Grid with structure form especially in paraffin zone was applied to reach the accurate solution. The numerical approach has high accuracy which was proved in verification section. Air becomes colder with going through the duct because of heat assimilating of NEPCM during charging. Elevating level of b causes decrement in time of melting around 45.26%. With augment of φ, the needed time declines less than 4.7% when distance of containers is 12.5 mm.